Thematic Progression Found in Students' Thesis Backgrounds at STKIP PGRI Sumatera Barat - Engla Okta Viska; Yelfiza Yelfiza; Siska Siska (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
This study is aimed at finding out paragraph coherence.  It is descriptive content analysis. Thirteen thesis backgrounds were chosen purposively based on the supervisors’ recommendation. Data were analyzed by coding, specify ing, and comparing. Then, the results indicate that every paragraph uses various thematic progression patterns. The patterns include CT, ZT, MS, CR, CP, DT, MP, LC, CL, and EP. The pattern determines the coherence level of the paragraph.